2004
DOI: 10.1159/000075052
|View full text |Cite
|
Sign up to set email alerts
|

Myoepithelioma Possibly Originating from the Accessory Parotid Gland

Abstract: Myoepithelioma originates almost exclusively from myoepithelial cells of the salivary, prostate and mammary glands. The skin is a very rare site where myoepithelioma occurs. We describe a patient with a myoepithelioma on the right cheek seen as a subcutaneous nodule that was separated from the parotid gland at surgical resection. Histopathological findings were consistent with those of a myoepithelioma that had originated from the parotid gland, suggesting that this tumor may have developed from the accessory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Most myoepitheliomas develop from the major salivary glands 5 . In addition, it can also develop within the prostate, mammary or sweat gland 6 . In our case, our patient showed a myoepithelioma on the palm, which contains numerous sweat glands.…”
mentioning
confidence: 56%
“…Most myoepitheliomas develop from the major salivary glands 5 . In addition, it can also develop within the prostate, mammary or sweat gland 6 . In our case, our patient showed a myoepithelioma on the palm, which contains numerous sweat glands.…”
mentioning
confidence: 56%
“…Only 5 cases of myoepithelioma of the APG have been reported in the English literature. Kawashima et al [4] reported a case in a 34-year-old woman, Isogai et al [2] reported a case of plasmacytoid myoepithelioma of the APG in a 47-year-old woman, and Sun et al [5] reported a case in a 41-year-old man and one in a 22-year-old woman; all of these cases were treated by surgery. Recently, Xie et al [3] described the fifth case in a 65-year-old man who was treated via an endoscopic approach.…”
Section: Discussionmentioning
confidence: 99%
“…The malignant transformation of epithelioid myoepithelioma has been described previously [2]. Complete resection along with the surrounding salivary tissue is recommended for myoepithelioma management in order to avoid tumor recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A tumor arising in an accessory parotid gland is rare. In the literature, several cases have been reported, the majority of them were epithelial tumors which were diagnosed as pleomorphic adenoma (9,10,11,12), myoepithelioma (13,14), mucoepidermoid carcinoma (15), and squamous cell carcinoma (16).…”
Section: Discussionmentioning
confidence: 99%